2022
DOI: 10.3389/fgene.2022.922019
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Targeting of Susceptibility Factor eIF4E-Enhanced Resistance Against Potato Virus Y

Abstract: Potato (Solanum tuberosum L.) is an important staple food around the world, and potato virus Y (PVY) is a major constraint for potato production. The VPg protein of PVY interacts with the translation initiation factor eIF4E of the host that works as a susceptibility factor during infection. The interaction between eIF4E and VPg was disrupted by CRISPR/Cas9. The homozygous conserved region of eIF4E of the potato variety “Kruda” was mutated by CRISPR/Cas9. Tracking of insertion, deletion, and conversion events w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…RNA viruses hijack host cellular machinery, including eIF4E, eIF4G, and their isoforms, to complete their life cycle (Sanfacon, 2015). Different isoforms of eIF4E were targeted by CRISPR/Cas9 to generate resistant varieties in tomato, potato, and cucumber against viruses belonging to Potyviridae (Chandrasekaran et al, 2016;Atarashi et al, 2020;Yoon et al, 2020;Lucioli et al, 2022;Noureen et al, 2022).…”
Section: Crispr/cas Mediated Resistance Against Virusesmentioning
confidence: 99%
“…RNA viruses hijack host cellular machinery, including eIF4E, eIF4G, and their isoforms, to complete their life cycle (Sanfacon, 2015). Different isoforms of eIF4E were targeted by CRISPR/Cas9 to generate resistant varieties in tomato, potato, and cucumber against viruses belonging to Potyviridae (Chandrasekaran et al, 2016;Atarashi et al, 2020;Yoon et al, 2020;Lucioli et al, 2022;Noureen et al, 2022).…”
Section: Crispr/cas Mediated Resistance Against Virusesmentioning
confidence: 99%
“…They found that only the TaeIF4E triple mutant was completely resistant to WYMV and set fruit normally; the single or double mutant remained susceptible and showed dwarf plants and severely reduced fruit set after susceptibility [ 66 ]. Not only has multi-gene editing been used on a large scale in major crops, but new superior traits have been created through multi-gene editing in a variety of crops such as tomatoes, apples, bananas, and potatoes ( Solanum tuberosum L.) [ 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Advances In Crispr/cas9 Gene Editing Technology In the Field...mentioning
confidence: 99%
“…RNA viruses need plant host factors to preserve their normal life cycle, containing the eukaryotic translation initiation factors eIF4E , eIF4G , and eIF(iso)4E [ 138 ]. Host susceptibility gene eIF4E was targeted at two different sites to create resistance against plant potyviruses by CRISPR/Cas9 [ 52 , 98 , 99 ]. A similar approach in A. thaliana plants induced site-specific mutations at eIF(iso)4E locus and conferred complete resistance to single-stranded RNA potyvirus -TuMV by 1 bp deletions and 1 bp insertions without any off-target modification [ 95 ].…”
Section: Crispr/cas Technique For Disease Resistancementioning
confidence: 99%